2012
DOI: 10.1159/000335240
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium in the First Week of Life in Extremely Low Birth Weight Infants

Abstract: Background: Evidence that antenatal administration of magnesium sulfate (MgSO4) to women in preterm labor may confer fetal neuroprotection is growing. MgSO4 crosses the placenta and can affect the neonate. Magnesium homeostasis in extremely low birth weight (ELBW) infants remains to be clarified. Objectives: We aimed to assess the natural progression of serum magnesium (Mg) in ELBW infants not exposed to antenatal MgSO4 during the first month of life. Methods: Laboratory data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The effect of antenatal MgSO 4 on magnesium homeostasis requires further study. 21,29 In no exposed group, Mg was 1.92 mg/dL AE 0.25 in day 1 and 2.33 mg/dL AE 0.38 in day 2 and in treated group, Mg was 2.68 mg/dL AE 0.52 and 2.60 mg/dL AE 0.35, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of antenatal MgSO 4 on magnesium homeostasis requires further study. 21,29 In no exposed group, Mg was 1.92 mg/dL AE 0.25 in day 1 and 2.33 mg/dL AE 0.38 in day 2 and in treated group, Mg was 2.68 mg/dL AE 0.52 and 2.60 mg/dL AE 0.35, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Mg then stabilizes toward the 66 hours of life in the exposed group and toward the 14 hours in the nonexposed, different from other publications. 21 Other than the dose regimens, factors such as gestational age, birth weight, and maternal serum magnesium levels, may influence the higher fetal serum magnesium. Renal clearance of magnesium in the initial days of life is decreased in neonates and especially in preterm neonates, causing the levels of magnesium to remain high for long periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports on changes in magnesium levels after birth have presented mixed findings. For instance, some authors did not find any changes in the levels of magnesium in the first week of life ( 8 ), others have stated that levels rise initially and subsequently stabilize ( 9 ). Furthermore, there is little consensus on addressing hypomagnesemia in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers have used magnesium supplements for hypomagnesemia ( 10 ), others found that low Mg levels became normal even in the absence of treatment ( 11 ). The need for more studies to understand magnesium homeostasis has also been highlighted by researchers ( 9 ).…”
Section: Introductionmentioning
confidence: 99%